2014
DOI: 10.1590/s1413-70542014000300008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phytic acid from rice and corn on morphology, cell proliferation, apoptosis and cyclooxygenase-2 expression in swine jejunal explants

Abstract: Phytic acid (IP6) is a potent antioxidant present in several natural foods. Beneficial effects on colon cancer and inflammation have been associated to IP6 in several studies, however, scarce data about the effect on small intestine are available. The aim of the present study was to evaluate the effect of different doses of IP6 from rice and corn on intestinal morphology, cellular proliferation, apoptosis and cyclooxygenase-2 (Cox-2) expression using swine jejunal explants as experimental model. This report de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This effect could be evaluated by an increase in the histological score and the villi height in explants exposed to IP6. In a previous experiment, we observed that doses of 2.5 mM and 5 mM IP6 improved the intestinal morphology and villi height of jejunal explants submitted to hypoxia [45] . IP6 likely acts on intestinal morphology by inhibiting the ribotoxic stress and lipid peroxidation caused by DON and FB1, respectively, through its antioxidant action.…”
Section: Discussionmentioning
confidence: 78%
“…This effect could be evaluated by an increase in the histological score and the villi height in explants exposed to IP6. In a previous experiment, we observed that doses of 2.5 mM and 5 mM IP6 improved the intestinal morphology and villi height of jejunal explants submitted to hypoxia [45] . IP6 likely acts on intestinal morphology by inhibiting the ribotoxic stress and lipid peroxidation caused by DON and FB1, respectively, through its antioxidant action.…”
Section: Discussionmentioning
confidence: 78%
“…Phytic acid, being a natural plant antioxidant possesses the ability to terminate the series of chain reaction [64]. It inhibits iron catalyzed hydroxyl radical (OH À ) formation [65].…”
Section: Antioxidant Role Of Phytic Acidmentioning
confidence: 99%
“…These results demonstrated that IP6 modulates apoptosis to protect cells and to prevent the development of disease. In a previous study, our group showed a protective effect of IP6 against the cellular hypoxia‐induced intestinal morphological changes of pigs (Silva and others a). In addition, we were able to demonstrate decreases in cell proliferation, apoptosis, and the expression of cyclooxygenase‐2 (Cox‐2) (Silva and others ).…”
Section: Effects In Other Pathological Conditionsmentioning
confidence: 81%